Effects of rivastigmine on visual attention in subjects with amnestic mild cognitive impairment: A serial functional MRI activation pilot-study. (30th March 2016) - Bokde, Arun L.W.; Cavedo, Enrica; Lopez-Bayo, Patricia; Lista, Simone; Meindl, Thomas; Born, Christine; Galluzzi, Samantha; Faltraco, Frank; Dubois, Bruno; Teipel, Stefan J.; Reiser, Maximilian; Möller, Hans-Jürgen; et al.
Abstract: A pilot study to investigate the effects of rivastigmine on the brain activation pattern due to visual attention tasks in a group of amnestic Mild Cognitive Impaired patients (aMCI). The design was an initial three-month double blind period with a rivastigmine and placebo arms, followed by a nine-month open-label period. All patients underwent serial functional magnetic resonance imaging (fMRI) at baseline, and after three and six months of follow-up. Primary endpoint was the effect of rivastigmine on functional brain changes during visual attention (face and location matching) tasks. There were five in the rivastigmine arm and two in the placebo arm. The face matching task showed higher activation of visual areas after three months of treatment but no differences compared to baseline at six months. The location matching task showed a higher activation along the dorsal visual pathway at both three and six months follow ups. Treatment with rivastigmine demonstrates a significant effect on brain activation of the dorsal visual pathway during a location matching task in patients with aMCI. Our data support the potential use of task fMRI to map specific treatment effects of cholinergic drugs during prodromal stages of Alzheimer's disease (AD). Highlights: The potential beneficial use of cholinesterase-inhibitors in mild cognitive impairment (MCI) is an unresolved issue. We examined practicality of performing a neuroimaging-drug study over 1 year. Primary endpoint was the effect of rivastigmine on functional brain changes during visual attention. The face matching task showed higher activation of early visual areas after three months of treatment but no differences compared to baseline at six months. The location matching task showed a higher activation along the dorsal visual pathway at both three and six months follow ups.